Development of dumbbell-shaped La2Si2O7:Eu3+ nanocrystalline phosphors for solid-state lighting applications. Issue 4 (15th February 2021) - Rama Raju, Ganji Seeta; Pavitra, Eluri; Hwang, Seung Kyu; Song, Young Hyun; Park, Jin Young; Chodankar, Nilesh R.; Ranjith, Kugalur Shanmugam; Huh, Yun Suk; Han, Young-Kyu
Abstract: There are ongoing efforts to develop novel phosphors with the properties required to make an object look as natural as it does under sunlight. It has been proven that particle morphology influences the luminescent properties of a phosphor. The rare-earth pyrosilicates, such as La2 Si2 O7 (LSO) are currently regarded as novel promising scintillators and protective pigments because of their good chemical and thermal stabilities. However, to date, there have been no reports available on the definite morphology of the LSO matrix and the precise luminescent properties of the trivalent europium (Eu 3+ )-doped LSO phosphor. Herein, we report the development of Eu 3+ -activated dumbbell-shaped LSO nanocrystalline phosphors using a two-step solvothermal and hydrothermal approach. After regrowth, the amorphous natured LSO:Eu 3+ precursor was transformed into well-defined LSO:Eu 3+ dumbbell-shaped nanocrystalline phosphors (LSO-R:Eu 3+ ) with a pure monoclinic phase. The phase purity was verified by Rietveld refinement analysis. The formation mechanism of the dumbbell-shaped particles was evaluated using surface morphological studies, and the involvement of the crystal splitting mechanism was established. The luminescence spectra revealed robust red emission at 614 nm under ultraviolet (UV) and near-UV excitations. The dipole-dipole interactions between the neighboring Eu 3+ ions induced the concentration quenching in LSO host matrix. Chromaticity coordinates (0.645, 0.342) emerged in the reddish-orange region and were comparable to the standard-definition and high-definition digital television coordinates (0.640, 0.330). Therefore, these results indicate that the synthesized LSO-R:Eu 3+ dumbbell-shaped nanocrystalline phosphor is a promising auxiliary red component for assembling desired white light-emitting diodes for indoor illuminations.